Finansowanie nieruchomości za pomocą kredytu bankowego wobec braku stabilności finansowej a problem bezpieczeństwa konsumenta - Czechowska, Iwona D. (Annales. Etyka w Życiu Gospodarczym, 2010)
The access of Poland to the EU caused the creation of the consumer protection system which consists of legal controls and different institutions such as e.g. UOKiK, BA, RZu. The aim of the study is to show problem of protection of bank services market consumer. The range of bank services is limited here to mortgage loans. Changes on the mortgage loan market in Poland during 2005–2008 are analysed in this work. The crisis on financial markets and its consequences have also been considered. The author presents the bank actions in the face of consumers during the crisis and the possibilities of the solving the disputes with dissatisfied consumers.